Feeding and oviposition behavior of Compsus viridivittatus (Coleoptera: Curculionidae) on species of citrus - GALLEGO-C., JEISSON STEEVENS; CAICEDO, ANA MILENA; CARABALÍ, ARTURO; MUÑOZ, JAIME EDUARDO (Revista Colombiana de Entomología, 2012)
Compsus viridivittatus (Coleoptera: Curculionidae) is one of the key pests of citrus in Colombia. Larvae consume roots and the adults leaves, flowers and fruits. It causes losses by decreases in leaf area greater than 50% in young trees and 20-30% in production trees. To determine feeding and oviposition preferences in commercial varieties, six varieties of citrus were used: valencia orange Citrus sinensis, sweety orange C. sinensis, arrayana mandarin C. reticulata, tahití lime C. latifolia, bird lime C. aurantiifolia and volkameriana rootstock C. volkameriana. Leaf consumption was evaluated through no-choice and free-choice trials. Oviposition preference was determined through no-choice trials. C. viridivittatus fed on all of the materials evaluated. In free-choice, C. viridivittatus showed preference for valencia orange (644 mm2) and lower consumption in mandarin (44 mm2). In no-choice, no significant differences were detected in the evaluated materials. The greatest oviposition (37 eggs) was observed when C. viridivittatus fed on bird lime, being significantly lower in tahití lime (9 eggs). The results obtained in this study contribute to the guiding of integrated pest management programs that allow for the reduction of C. viridivittatus populations.